Streetwork at the crossroads: an evaluation of a street gang outreach intervention and holistic appraisal of the research evidence - Hureau, David M. (Criminology, 2023)
Spurred by the success of public health violence interventions, and accelerated by policy pressure to reduce violence without exacerbating overpolicing and mass incarceration, streetwork programs—those that provide anti-violence services by neighborhood-based workers who perform their work beyond the walls of parochial institutions—have positioned themselves as the most important non-law-enforcement violence prevention option available to urban policy makers. Yet despite their importance, the state of the field seems difficult to interpret for academics and practitioners alike. In this article, we make several contributions that bring forth new findings and deliver new perspectives on streetwork as a violence reduction strategy. First, we offer an extended analytic review of the streetwork evaluation literature that connects the study of contemporary public health violence interventions to a preceding tradition of criminologically inspired streetwork studies. Second, we present the results of an impact evaluation of StreetSafe Boston (SSB)—a multiyear streetwork intervention that served 20 Boston gangs. We find that the SSB intervention had no detectable effect on violence among the gangs that it served. We conclude by offering a framework for understanding a field at multiple crossroads: past and present, proclaimed successes and failures, help and harm.